The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.18869/acadpub.irjns.1.2.31
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Outcome of Chronic Subdural Hematoma in Sub-Saharan Afrcia and the Country of Benin

Abstract: Background & Aim: Chronic subdural hematoma (CSDH) is a common neurosurgical pathology. The objective of this study was to describe the epidemiology of this pathology and the results in treating it combined from three hospital centers in Benin. Methods & Materials/Patients: From September 2010 to September 2013 a multi-center, retrospective and descriptive study was conducted in three hospital centers in Benin. Inventory was taken of all patients in whom CSDH was diagnosed. Patients were evaluated according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…A study has attributed the lower incidence of CSDH in females to the protective effect of estrogen on capillaries and the relatively wider intracranial radius in males [ 19 ]. The male to female ratio was similar to those reported in other studies in West Africa and other parts of the world [ 4 , 16 , 20 ]. It was however different from the findings of Dakurah et al [ 17 ], in a retrospective study done 20 years ago at the same study site where a male to female ratio of 16:1 was reported.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A study has attributed the lower incidence of CSDH in females to the protective effect of estrogen on capillaries and the relatively wider intracranial radius in males [ 19 ]. The male to female ratio was similar to those reported in other studies in West Africa and other parts of the world [ 4 , 16 , 20 ]. It was however different from the findings of Dakurah et al [ 17 ], in a retrospective study done 20 years ago at the same study site where a male to female ratio of 16:1 was reported.…”
Section: Discussionsupporting
confidence: 89%
“…However, the percentage of hypertensives in this study is much higher than previous studies done in west Africa. Dakurah et al had 9.7% in Accra, Bankole et al had 22.9% in Lagos, Jimoh et al had 23.3% in Zaria and Chikani et al had 15.87% in Enugu [ 16 , 17 , 20 – 23 ]. The higher percentage of hypertensives found in this study is however consistent with a recent multi-centre report from Eastern Europe which indicated that as high as 75% of patients with CSDH were hypertensives [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, a younger cohort is observed, and it is thought that this may be due to the increased incidence of trauma in the region as well as a lower life expectancy compared to the higher-income countries [6,7,10]. The challenges of accessibility to diagnostic imaging services, due to financial constraints or more simply availability, have also been discussed in African literature [12,13]. The availability of neurosurgical expertise on the continent is far below that required to meet the demand; in some African countries, successful treatment of this intracranial bleed is carried out by general surgeons [14].…”
Section: Introductionmentioning
confidence: 99%